2009
DOI: 10.1063/1.3268787
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of indium-tin-oxide Schottky contacts to ZnMgO/ZnO heterojunctions with band gap grading

Abstract: We report on electrical characteristics of indium-tin-oxide (ITO) Schottky contacts to transparent n-n isotype heterojunctions composed of a compositionally graded Zn1−xMgxO (g-ZnMgO) and ZnO films fabricated on ITO-coated glass substrates. The transparent ITO Schottky contacts to g-ZnMgO/ZnO heterostructures resulted in excellent diode characteristics with the rectification ratios as high as 104 at a bias voltage of ±3.0 V. The effective Schottky barrier heights were about 0.6 eV and could be tuned by modifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Therefore, the ITO film of this study is believed to be partially crystallized, so that the resistance of the film is varying laterally. For instance, S. Bowden et al [6] reported a simulation result on the exactly same phenomenon that I-V curve seems to have a very low shunt resistance when a very high resistance, for example 150 ohm, affects a small portion as much as 10% of the cell. This means that the effect is due solely to the lateral non-uniformity of sheet resistance of ITO.…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, the ITO film of this study is believed to be partially crystallized, so that the resistance of the film is varying laterally. For instance, S. Bowden et al [6] reported a simulation result on the exactly same phenomenon that I-V curve seems to have a very low shunt resistance when a very high resistance, for example 150 ohm, affects a small portion as much as 10% of the cell. This means that the effect is due solely to the lateral non-uniformity of sheet resistance of ITO.…”
Section: Resultsmentioning
confidence: 89%
“…It should follow that if electrons need to overcome a Schottky barrier in order to be injected from the Zn 0.8 Mg 0.2 O to the ITO, the current density–voltage ( J – V ) curve should display rectifying behavior. 25 Unexpectedly, this rectification is absent, with a linear J – V plot (Figure 2 b) exhibited. 26 A linear J – V curve in the presence of a Schottky barrier may be due to (i) the Zn 0.8 Mg 0.2 O Fermi level being pinned by surface states, leading to no band-bending, 26 , 27 (ii) the potential difference between Zn 0.8 Mg 0.2 O and ITO being screened as a result of surface dipoles introduced by localized surface states 27 or (iii) charge tunneling through the Schottky barrier, either directly or via trap states extending below the band-edge of the Zn 0.8 Mg 0.2 O.…”
Section: Resultsmentioning
confidence: 90%
“…The rectifying characteristic of the device is attributed to the graded band gap of g -Al:ZnMgO, causing highly asymmetric Schottky barrier heights at the electrode contacts [ 29 ]. The current in the positive bias region increases rapidly above a voltage of ~3.5 V and I - V curves become quite asymmetric, resulting in the rectifying behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Advances in thin film technology have enabled the fabrication of well-controlled graded band gap semiconductor systems [ 22 , 23 ]. Regarding oxide materials, deposition of epitaxial films with graded composition is possible when the constituent materials of the films are isomorphic [ 28 , 29 , 30 ]. During this experiment, g- Al:MgZnO films are deposited using AACVD, as shown schematically in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%